Effect of Garlic (Allium sativum) and Tulsi (Ocimum sanctum) Leaf Powder Supplementation on Growth Performance and Carcass Traits in Broiler Chicken - Kumar, Rakesh; Maan, N.S.; Sihag, Sajjan; Sheoran, Nancy; Baloda, Saurabh; ., Promila; Shunthwal, Jyoti (Indian Journal of Animal Nutrition, 2018)
The experiment was designed to evaluate the effect of supplementing different levels of garlic and tulsi (Ocimum sanctum) leaf powder in diet on growth performance and carcass yields in broiler chicken. A total of 280 day-old commercial broiler chicks (Vencobb-400) were randomly distributed into seven treatments, each treatment had four replicates with ten chicks in each replicate. The control group T1 was fed a basal diet formulated as per BIS (2007) while in treatment groups T2 and T3 basal diet was supplemented with garlic powder @ 0.5 and 1%; T4 and T5 were supplemented with tulsi leaf powder @ 0.5 and 1%; and chicks of T6 and T7 were fed diets supplemented with combinations of garlic powder and tulsi leaf powder @ 0.5 and 1.0% of each, respectively. The body weight gain was (P<0.05) higher in broilers fed diet supplemented with combination of garlic powder and tulsi leaf powder as compared to other treatment groups. Feed intake was not affected significantly, however, feed conversion ratio improved (P<0.05) in supplemented groups with combinations of garlic powder and tulsi leaf powder at 0.5 and 1.0% of each as compared to other groups. The dressing and eviscerated per cent was higher (P<0.05) in supplemented groups with combinations of garlic powder and tulsi leaf powder at 0.5 and 1.0% of each and lowest in control group but the per cent of liver, heart and gizzard was similar in all the treatments. Per cent values for abdominal fat were lower (P<0.05) in 1% garlic powder, 1% tulsi leaf powder and combination of garlic powder and tulsi leaf powder at 0.5% each supplemented groups as compared to that with 1% combination supplemented group. Thus, supplementation of mixture of garlic and tulsi leaf powder at 0.5 each or 1.0% each in the broilers diet significantly improved body weight gain, feed conversion ratio, dressing yield, eviscerated per cent while lowering abdominal fat per cent without affecting feed intake.